2023
DOI: 10.3390/molecules28041886
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Composite of Sn(IV)-Porphyrin and Mesoporous Structure for Enhanced Visible Light Photocatalytic Degradation of Organic Dyes

Abstract: Two hybrid composites (SnP@MCM−41 and SnP@SiO2) were fabricated by chemical adsorption of (trans-dihydroxo)(5,10,15,20-tetraphenylporphyrinato)tin(IV) (SnP) on mesoporous structured Mobil Composition of Matter No. 41 (MCM−41) and SiO2 nanoparticles. These materials were characterized by Fourier-transform infrared spectroscopy, ultraviolet–visible spectroscopy, fluorescence spectroscopy, transmission electron microscopy, and field-emission scanning electron microscopy techniques. The incorporation of SnP into M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Interestingly, SnP underwent dramatic weight loss starting only at 350 °C. 55 To investigate the chemical stability of SnPOP, different chemical environments, including different aqueous and organic solvents, were used to expose the SnPOP samples for 24 h. It was observed that SnPOP swelled in THF, DCM, acetone, and ethyl acetate, while retaining its gel form (Fig. S2 †).…”
Section: Syntheses and Spectroscopic Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, SnP underwent dramatic weight loss starting only at 350 °C. 55 To investigate the chemical stability of SnPOP, different chemical environments, including different aqueous and organic solvents, were used to expose the SnPOP samples for 24 h. It was observed that SnPOP swelled in THF, DCM, acetone, and ethyl acetate, while retaining its gel form (Fig. S2 †).…”
Section: Syntheses and Spectroscopic Characterizationmentioning
confidence: 99%
“…It is important to note that we did not use any capping agent like poly(N-vinyl pyrrolidone) (PVP) or any surfactants. 53,55 The use of surfactants such as sodium dodecyl sulphate (SDS) makes it difficult to separate Ag NPs from the reaction mixture. We examined the optical and surface properties of the as-prepared Ag NPs using UV-vis spectrophotometry, FE-SEM/EDS, and TEM.…”
Section: Photocatalytic Fabrication Of Ag Nanoparticlesmentioning
confidence: 99%
“…In comparison with the previous investigations, the Amaranth dye degradation for sample S3 is significantly higher (Table 3). [39][40][41][42][43][44] This is most likely due to the better response of S3 photocatalyst to visible light due to its lower bandgap, which allows the bulk of visible light to be consumed and generates a significant number of electron-hole pairs.…”
Section: Min By S3mentioning
confidence: 99%
“…Previously, we and others immobilized Sn(IV)porphyrins on TiO 2 to construct nanohybrid materials for photocatalysis [36][37][38]. Sn(IV)porphyrin complexes were selected because they are outstanding building blocks for constructing functional porphyrin nanomaterials for the photocatalytic degradation of organic pollutant dyes [39][40][41][42][43][44]. Sn(IV)porphyrin centers are oxophilic and can form stable 6-coordinate complexes with two trans-axial oxyanion ligands (alkoxides and carboxylates) [45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%